2014
DOI: 10.2516/ogst/2013200
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation and Dissociation in the Presence of Silica Sand and Bentonite Clay

Abstract: and available online here Cet article fait partie du dossier thématique ci-dessous publié dans la revue OGST, Vol. 70, n°6, pp. 909-1132 et téléchargeable ici D o s s i e rOil & Gas Science and Technology -Rev. IFP Energies nouvelles, Vol. 70 (2015), No. 6, pp. 909-1132 Copyright © 2015, IFP Energies nouvelles > Editorial -Enhanced Oil Recovery (EOR), Asphaltenes and HydratesÉditorial -EOR «récupération assistée du pétrole», Asphaltènes et Hydrates D. Langevin and F. Baudin ENHANCED OIL RECOVERY (EOR) > HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The bottleneck of this potential technology, however, is the slow kinetics of MH formation at bulk conditions, lowering its competitiveness against other technologies dramatically. Fortunately, MH formation was found to be promoted in confined spaces of porous materials, such as silica, clays, , metal-organic frameworks, or activated carbons. Among them, activated carbons with high internal surface area are the most promising materials for this particular application since they have proven to enhance the formation kinetics of MH from days to minutes . Although methane storage via physisorption can enhance storage capacity compared to compression at moderate pressure, the amount of methane stored in prehumidified carbons surpasses the amount stored in the corresponding dry materials considerably. , …”
Section: Introductionmentioning
confidence: 99%
“…The bottleneck of this potential technology, however, is the slow kinetics of MH formation at bulk conditions, lowering its competitiveness against other technologies dramatically. Fortunately, MH formation was found to be promoted in confined spaces of porous materials, such as silica, clays, , metal-organic frameworks, or activated carbons. Among them, activated carbons with high internal surface area are the most promising materials for this particular application since they have proven to enhance the formation kinetics of MH from days to minutes . Although methane storage via physisorption can enhance storage capacity compared to compression at moderate pressure, the amount of methane stored in prehumidified carbons surpasses the amount stored in the corresponding dry materials considerably. , …”
Section: Introductionmentioning
confidence: 99%
“…Figure b depicts a 1.92% deviation for the developed model from the actual data points, whereas it is 5.46% for the existing model. This is because the rigorous model takes into account most of the practical issues related to the hydrate growth in marine sediment …”
Section: Resultsmentioning
confidence: 99%
“…This is because the rigorous model takes into account most of the practical issues related to the hydrate growth in marine sediment. 49 3.1.2. Hydrate Formation in Seawater.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the confined spaces of porous materials promote methane hydration formation. Activated carbons, silica, clay, , and metal–organic frameworks (MOFs) are used as potential porous materials, which are used in hydration technology. Activated carbons, possessing a high internal surface area in favor of enhancement of hydration formation, are considered as the most favorable materials for the respective application as they can reduce the methane hydration process from days to minutes …”
Section: Resultsmentioning
confidence: 99%